2017
DOI: 10.17957/tpmj/17.3499
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Shaft Fractures; Epidemiology, a 5-Year Study in Ghurki Trust Teaching Hospital, Pakistan.

Abstract: ORIGINAL PROF-3499 ABSTRACT… Background: Tibia is the most commonly fractured bone because of its structure and position. Tibial fractures are increasing with time to time and hence the morbidity and mortality are increasing despite proper public health efforts. There is a lack of national epidemiological data on the characteristics of patients with tibial shaft fractures. Therefore, epidemiological assessment is crucial for fracture. The purpose of this study was to provide upto-date information about patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The findings were similar to what was reported in Aman et al study, in which the majority were motorbike accidents with a prevalence of around 67%. 10 However, the prevalence of RTA pedestrians was around 8%. 10 The higher prevalence of RTA pedestrians in our study could be due to various reasons, including suboptimal road conditions, lack of footpaths, road rage, and negligence of traffic safety rules and regulations.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The findings were similar to what was reported in Aman et al study, in which the majority were motorbike accidents with a prevalence of around 67%. 10 However, the prevalence of RTA pedestrians was around 8%. 10 The higher prevalence of RTA pedestrians in our study could be due to various reasons, including suboptimal road conditions, lack of footpaths, road rage, and negligence of traffic safety rules and regulations.…”
Section: Discussionmentioning
confidence: 98%
“…10 However, the prevalence of RTA pedestrians was around 8%. 10 The higher prevalence of RTA pedestrians in our study could be due to various reasons, including suboptimal road conditions, lack of footpaths, road rage, and negligence of traffic safety rules and regulations. [14][15][16][17] This study identified that the prevalence of left-sided tibia fractures was slightly higher than right-sided tibia fractures (52.39% vs. 44.84%).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The increased number of tibial fractures over time results in increased morbidity and disability rates. Fracture is one of the problems that humans are faced with in a risky life because of the development of the industrialisation of society, the increasing number of vehicles, and increased activity [1]. The incidence of tibial fracture is recorded at 16.9/100,000 per year [2].…”
Section: Introductionmentioning
confidence: 99%